2000
DOI: 10.1111/j.8755-8920.2000.440302.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐DNA Antibodies Cross‐reacting with Laminin Inhibit Trophoblast Attachment and Migration: Implications for Recurrent Pregnancy Loss in SLE Patients

Abstract: These studies suggest that anti-DNA antibodies cross-reacting with LNs may play a role in early pregnancy failure in SLE patients by interfering with placental implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 24 publications
1
33
0
Order By: Relevance
“…1 An association between autoantibodies and gestational loss has been identifi ed, especially for antiphospholipid antibodies (APA). Other antibodies such as those against thyroid components, nuclear antigens and deoxyribonucleic acid (DNA) fractions 2 have also been associated with gestational loss and preeclampsia. 3 Venous thrombosis in the mother has been associated with RSA in several series.…”
Section: Introductionmentioning
confidence: 99%
“…1 An association between autoantibodies and gestational loss has been identifi ed, especially for antiphospholipid antibodies (APA). Other antibodies such as those against thyroid components, nuclear antigens and deoxyribonucleic acid (DNA) fractions 2 have also been associated with gestational loss and preeclampsia. 3 Venous thrombosis in the mother has been associated with RSA in several series.…”
Section: Introductionmentioning
confidence: 99%
“…These immune complexes were observed as electron-dense structures in GBMs and the mesangial matrix, and bound IgG was confined to electron-dense structures in both murine (12,14) and human (13) lupus nephritis. In vivo bound IgG was not observed in regular glomerular structures (15), although anti-DNA antibodies have been shown to cross-react in vitro with other glomerular antigens (16)(17)(18)(19). It is unclear whether antibodies form complexes with chromatin in circulation or in situ in glomeruli.…”
mentioning
confidence: 99%
“…However, the pathways by which these antibodies act as a pathogenic factor are controversial. Diverse models have been suggested that involve interaction pathways that differ from pure antibody binding to their homologous antigens (dsDNA or nucleosomes [7,[10][11][12][13]), to cross-reactions with glomerular constituents such as ␣-actinin (14,15), laminin (16)(17)(18), mesangial cells (19,20), or mesangial matrix structures (19,21,22). Because one therapeutic strategy may be to inhibit complex formation of antinucleosome antibodies with their glomerular target antigens, it is crucial to determine the nature of these structures.…”
mentioning
confidence: 99%